Water Quality Analysis and Water Pollution Effect from Upstream to Downstream of Brantas River - East Java - Rony Irawanto; Alfin Fatwa M Afifudin; Anggraini Aurina Putri; Nadila Wulan Cahyani; Farhani Nurshafa Rahmania; Soemarno; Amin Setyo Leksono; Bagyo Yanuwiadi; Catur Retnaningdyah; Harsuko Riniwati; Sugiyanto (Jurnal Pembangunan dan Alam Lestari)
Brantas River is the largest river in East Java, flowing from the city of Batu upstream until downstream in Surabaya and Sidoarjo. This river plays a crucial role as a vital natural resource that supports the various needs of the surrounding communities. This study serves as a preliminary investigation with the primary aim of assessing the water quality in three different zones of the Brantas River: the upper, middle, and downstream sites. Additionally, this research includes a review to identify the organisms exposed to water pollution in the Brantas River. The study was conducted from November 2020 to April 2023, utilizing an exploratory observational method at 19 observation stations. The data obtained was subsequently analyzed using a descriptive approach. Various parameters were observed, including pH (a measure of acidity or alkalinity), hardness (the concentration of calcium and magnesium ions), alkalinity (the capacity of water to neutralize acids), nitrate, nitrite, fluoride, and heavy metals such as lead (Pb), copper (Cu), and iron (Fe). The research findings indicate that in several upstream areas of the Brantas River, there were elevated hardness, nitrate, lead (Pb), and iron (Fe) that exceeded the established water quality standards. In the middle section of the river, water quality was generally satisfactory, although a few locations exhibited slightly elevated levels of lead (Pb). Meanwhile, all locations downstream of the Brantas River demonstrated water quality that exceeded the prescribed standards. After a literature review, it was discovered that various biota in the Brantas River have been exposed to pollutants, including fish species and plants like Ipomea aquatica and Eichhornia crassipes. Therefore, it is necessary and urgent to improve water management and monitoring plants and biota in the Brantas River to preserve organisms in aquatic and terrestrial ecosystems.